Deficient CD40-TRAF6 signaling in leukocytes prevents atherosclerosis by skewing the immune response toward an antiinflammatory profile - Lutgens, Esther (The Rockefeller University Press, 2010)
The CD40–CD40 ligand (CD40L) signaling axis plays an important role in immunological pathways. Consequently, this dyad is involved in chronic inflammatory diseases, including atherosclerosis. Inhibition of CD40L in apolipoprotein E (Apoe)–deficient (Apoe(−/−)) mice not only reduced atherosclerosis but also conferred a clinically favorable plaque phenotype that was low in inflammation and high in fibrosis. Blockade of CD40L may not be therapeutically feasible, as long-term inhibition will compromise systemic immune responses. Conceivably, more targeted intervention strategies in CD40 signaling will have less deleterious side effects. We report that deficiency in hematopoietic CD40 reduces atherosclerosis and induces features of plaque stability. To elucidate the role of CD40–tumor necrosis factor receptor-associated factor (TRAF) signaling in atherosclerosis, we examined disease progression in mice deficient in CD40 and its associated signaling intermediates. Absence of CD40-TRAF6 but not CD40-TRAF2/3/5 signaling abolishes atherosclerosis and confers plaque fibrosis in Apoe(−/−) mice. Mice with defective CD40-TRAF6 signaling display a reduced blood count of Ly6C(high) monocytes, an impaired recruitment of Ly6C(+) monocytes to the arterial wall, and polarization of macrophages toward an antiinflammatory regulatory M2 signature. These data unveil a role for CD40–TRAF6, but not CD40–TRAF2/3/5, interactions in atherosclerosis and establish that targeting specific components of the CD40–CD40L pathway harbors the potential to achieve therapeutic effects in atherosclerosis.